A case of paramyotonia congenita in pregnancy. (December 2020) - Brooks, EK; Schweitzer, D; Robinson, HL
Paramyotonia congenita is a rare autosomal dominant non-dystrophic myopathy caused by mutations in the SNC4A gene, which encodes for the voltage-gated sodium channel in skeletal muscle. Symptom onset is typically during early childhood and is characterised by myotonia followed by flaccid paralysis or weakness, usually exacerbated by repeated muscle contractions or cold temperatures. Pregnancy has been reported to increase symptoms of myotonia; however, there is limited information in the literature regarding the possible effects of paramyotonia congenita on pregnancy and labour. We present a successful case of a 20-year-old primigravida with confirmed paramyotonia congenita and review the literature regarding paramyotonia congenita during pregnancy.